2019
DOI: 10.1002/cite.201800137
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Chemical Reaction Engineering and Process Intensification for the Lean Aqueous Hydroformylation Using a Jet Loop Reactor

Abstract: The biphasic hydroformylation of 1‐octene using a lean aqueous phase as solvent phase for catalyst recycling is discussed here. The gas‐liquid‐liquid reaction was homogeneously catalyzed by industrial standard catalytic system with [Rh(cod)Cl]2 as precursor and TPPTS as ligand. This work summarizes investigations addressing different aspects of the reaction, where a procedural approach was followed to gain understanding of its nature, kinetics and interphase reactivity. Finally, the application of the jet loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Jet loop reactors have been used for model reactions such as hydrogenation, chlorination, phosgenation, hydroformylation, 124,125 as well as for processes of CO 2 absorption, 126 anaerobic codigestion of olive mill wastewater and liquid poultry manure, 127 treatment of slaughterhouse wastewater, 128 imidacloprid preparation, 129 and microbial fermentation. Another Critical Look at Three-Phase Catalysis Ni e120…”
Section: Bubble Columnmentioning
confidence: 99%
“…Jet loop reactors have been used for model reactions such as hydrogenation, chlorination, phosgenation, hydroformylation, 124,125 as well as for processes of CO 2 absorption, 126 anaerobic codigestion of olive mill wastewater and liquid poultry manure, 127 treatment of slaughterhouse wastewater, 128 imidacloprid preparation, 129 and microbial fermentation. Another Critical Look at Three-Phase Catalysis Ni e120…”
Section: Bubble Columnmentioning
confidence: 99%
“…A promising strategy to improve the rates of a reaction without modification of the chemical properties of the system is to intensify the degree of mixing by means of the reactor design . Herein, the phase contacting is intensified using, for example, multiple stirrers, , various stirrer geometries in a stirred tank reactor, static mixer reactors, or ejector loop reactors. , …”
Section: Introductionmentioning
confidence: 99%
“…40 Herein, the phase contacting is intensified using, for example, multiple stirrers, 10,41 various stirrer geometries in a stirred tank reactor, 42 static mixer reactors, 43 or ejector loop reactors. 44,45 The aqueous biphasic hydroformylation of long-chain olefins has been discussed to take place either in the catalyst bulk phase or at the liquid−liquid (LL) interface, with the latter being favored in the literature on the basis of estimations of the Hatta number, a comparison of the reaction rates of olefins with different carbon chain lengths, an observed first-order dependence on the olefin concentration in the organic phase, and a proposed linear dependence of the rate of reaction on the LL interfacial area. 39,42,44,46 Recently, our group showed that, in a mixture of α-olefins of varying carbon chain lengths, the individual rates of conversion do not correlate with the individual water solubilities but with their respective mole fraction in the organic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, multiple investigations on reactor configurations have arisen to intensify the mixing. Various reviews cover intensified reactors such as fluidic oscillators based on the Coanda effect, 1 oscillatory baffled reactors, 2 devices to cause hydrodynamic cavitation 3 or a range of pulsating flows by ultrasound or mechanical vibration, 4 static mixer reactors, 5 microreactors, 5‐7 and ejector loop reactors 5,8 . Reactors based on the Taylor‐Couette flow (Taylor‐Couette reactors, TCRs) however are considered more scarcely, with the available reviews focusing more on the flow itself rather than the apparatus and its technical applications.…”
Section: Introductionmentioning
confidence: 99%